Complicaciones postquimioterapia en pacientes con diagnóstico de cáncer gástrico que actualmente reciben tratamiento en el Hospital Solca-Loja. - Fernández Chicaiza, Alex Darío (2016)
This research is a descriptive, comparative and qualitative study of the post-chemotherapy complications in patients diagnosed with gastric cancer currently receiving treatment in the hospital SOLCA- Loja for which a sample of 56 patients was taken in the period July-December 2015, in which a survey receiving chemotherapy treatment was applied. It was determined that gastric cancer has a distribution of 61% in men, while in women occurs in a lower percentage of 39%, plus the most frequent complications after post-chemotherapy are nausea and vomiting in a 88% weight loss, loss of hair 73% of cases and less frequent complications such as fever and presented palpitations. The drug most commonly used is 5 fluorouracil in 40% of patients and cisplatin by 19% in some cases they are used in combination or association with other chemotherapeutic agents according to the type of patient. Finally this study concluded that the drug major complications produced is 5 fluorouracil 63% (26 cases) of patients treated with the same followed by cisplatin with 60% (12 cases) oxaliplatin 70% (12 cases) and least complications occur are leucovorin 0% 0% capecitabine epirubicin 1-3 with 0% complications. Keywords: Gastric Cancer, fluorouracil, Cisplatin Chemotherapy.